2016
DOI: 10.1002/mc.22495
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitination of apurinic/apyrimidinic endonuclease 1 by Parkin

Abstract: Apurinic/apyrimidinic endonuclease 1 (APE1) is an essential protein crucial for repair of oxidized DNA damage not only in genomic DNA but also in mitochondrial DNA. Parkin, a tumor suppressor and Parkinson’s disease (PD) associated gene, is an E3 ubiquitin ligase crucial for mitophagy. While DNA damage is known to induce mitochondrial stress, Parkin’s role in regulating DNA repair proteins has not been elucidated. In this study, we examined the possibility of Parkin-dependent ubiquitination of APE1. Ectopicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 80 publications
2
12
0
Order By: Relevance
“…Growing evidence suggests that cisplatin would accumulate in and interact with various cell organelles in response to oxidative stress and unrelated or indirect DNA effects, such as reactive oxygen species (ROS) production . APE1 is an essential protein crucial for the repair of oxidized DNA damage not only in genomic DNA but also in mitochondrial DNA . In our previous work, we found that APE1 could translocalize to mitochondria after photodynamic therapy and protect cells from apoptosis .…”
Section: Discussionsupporting
confidence: 90%
“…Growing evidence suggests that cisplatin would accumulate in and interact with various cell organelles in response to oxidative stress and unrelated or indirect DNA effects, such as reactive oxygen species (ROS) production . APE1 is an essential protein crucial for the repair of oxidized DNA damage not only in genomic DNA but also in mitochondrial DNA . In our previous work, we found that APE1 could translocalize to mitochondria after photodynamic therapy and protect cells from apoptosis .…”
Section: Discussionsupporting
confidence: 90%
“…Another BER member, APE1, is regulated by Parkin an E3 ubiquitin ligase, which when mutated can cause autosomal recessive early onset PD (Shimura et al, 2000). Interestingly, APE1 is ubiquitinated in a Parkin‐dependent manner and PD‐causing mutations in Parkin abrogate this ubiquitination, resulting in APE1 accumulation (Scott et al, 2017). Genetic studies further support a role for BER variants in the development of PD.…”
Section: Ber and Dna Single‐strand Damagementioning
confidence: 99%
“…Specifically, acetylated residues (Lys27, Lys31, Lys32 and Lys35) are clustered in the protein N-terminus and are involved in protein-protein interactions [7], APE1 binding to RNAs and DNAs [35], endonuclease activity [5,15,35] and protein binding to nCaRE sequences [36]. Moreover, these residues are ubiquitinated by several ubiquitin ligases (e.g., MDM2, UBR3 and Parkin) [8,37,38], which thus control the steady state level of the protein. Additionally, APE1 enzymatic activities are controlled by interactions involving its N-terminal region [23].…”
Section: Discussionmentioning
confidence: 99%